A cross-sectional survey benchmarking the coverage and importance of obesity-related competencies in U.S. dietetic supervised practice programs - Rosanna P. Watowicz; Varsha Krishnan; W. Scott Butsch (BMC Medical Education)
Abstract Background Registered Dietitian Nutritionists (RDNs) have long been part of the interdisciplinary team recommended for obesity treatment. Obesity education for RDNs is important not only for ensuring adequate knowledge but also for reducing weight stigma. The objective of this study was to benchmark the inclusion of obesity-related competencies in dietetic supervised practice programs, as self-reported by supervised practice directors, to begin to understand the training that U.S. RDNs receive. Methods This was an exploratory, cross-sectional, online survey of U.S. dietetic supervised practice directors distributed in July of 2022. The directors were asked about the importance and extent of inclusion of 31 obesity-related competencies, as well as barriers for inclusion. The competencies were derived from the 2017 Provider Competencies on the Prevention and Management of Obesity. Results We received 36 survey responses, representing 10.4% of supervised practice directors in the U.S. Very few programs reported ‘not at all incorporated’ for any competencies; the most frequent were ‘potential role of genetics/epigenetics’ (15%, n = 5) and ‘physiology/pathophysiology of obesity’ (12%, n = 4). The competencies most frequently reported as ‘very important’ were ‘perform effectively in an interprofessional team’ and ‘discuss obesity in a non-judgmental manner’. Lack of time in the curriculum was the most frequently reported barrier. Conclusions For programs hoping to both expand obesity education and decrease weight stigma in a limited amount of time, improving coverage of competencies related to non-modifiable causes of obesity may be an area to prioritize.